Prevalência de pressão arterial elevada em escolares da rede pública no município de Santa Cruz, RN - Brito, Renatha Celiana da Silva (2017)
The aim of this study is to describe the frequency of blood pressure in schoolchildren from the public school system of Santa Cruz, Rio Grande do Norte and to compare methodological aspects and results to national and international research samples. This is a cross-sectional study with a quantitative approach and literature review preformed at PubMed between 1973 and 2017. Original cross-sectional papers with prevalence in percentage of high blood pressure (HBP), mean age between 5 and 10 years, full available and published in Portuguese, English and Spanish, were included. The sample consisted of 411 schoolchildren, mean age of 9.49 years, male and female, with 65.5% eutrophic. Of the sample, 63.5% presented normal BP (< 90th), 6.8% prehypertension or risk of developing hypertensive diseases (≥90th and <95th) and the prevalence of HBP or hypertension was 29.7% (>95th). Twelve articles were selected, the lower prevalence was found in Mexico (4.9%) and the higher one in Brazil (16.6%). These results highlight the need to promote government programs to prevent diseases in child population and to investigate the factors that may be involved in the fact that national studies have higher prevalence of HBP when compared to international ones.